(untitled) (Research, Society and Development, 2022)
The objective of this work is to present an experience of group welcoming in mental health in a Family Health Unit in the city of Vitória-ES, in partnership with a university extension project. The meetings were conducted by a psychologist and a Psychology undergraduate, held once a week, with an average duration of two hours and the participation of about five users. During these meetings, the main resource used was images extracted from magazines, with the aim of helping users to express themselves and talk about the reasons that led them to seek the health service. This host configuration proved to be quite powerful, as the participants felt comfortable talking about their anxieties, welcomed each other and exchanged experiences among themselves. By sharing with their peers, participants realized that their complaints were not only their own, but that they were also materialized in the lives of other people living in the same territory. In this sense, the participants did not occupy a passive place, but as autonomous subjects and protagonists of their health process. In addition, such a reception format contributed to broadening perspectives regarding the role of Psychology beyond traditional clinical care. However, there were also some challenges in carrying out such activity, especially with regard to conducting the group and the lack of infrastructure at the Family Health Unit.